Muscle atrophy‐related myotube‐derived exosomal microRNA in neuronal dysfunction: Targeting both coding and long noncoding RNAs. Issue 5 (31st March 2020) - Yang, Chia‐Pei; Yang, Wan‐Shan; Wong, Yu‐Hui; Wang, Kai‐Hsuan; Teng, Yuan‐Chi; Chang, Ming‐Hsuan; Liao, Ko‐Hsun; Nian, Fang‐Shin; Chao, Chuan‐Chuan; Tsai, Jin‐Wu; Hwang, Wei‐Lun; Lin, Ming‐Wei; et al.
Abstract: In mammals, microRNAs can be actively secreted from cells to blood. miR‐29b‐3p has been shown to play a pivotal role in muscle atrophy, but its role in intercellular communication is largely unknown. Here, we showed that miR‐29b‐3p was upregulated in normal and premature aging mouse muscle and plasma. miR‐29b‐3p was also upregulated in the blood of aging individuals, and circulating levels of miR‐29b‐3p were negatively correlated with relative appendicular skeletal muscle. Consistently, miR‐29b‐3p was observed in exosomes isolated from long‐term differentiated atrophic C2C12 cells. When C2C12‐derived miR‐29b‐3p‐containing exosomes were uptaken by neuronal SH‐SY5Y cells, increased miR‐29b‐3p levels in recipient cells were observed. Moreover, miR‐29b‐3p overexpression led to downregulation of neuronal‐related genes and inhibition of neuronal differentiation. Interestingly, we identified HIF1α‐AS2 as a novel c‐FOS targeting lncRNA that is induced by miR‐29b‐3p through down‐modulation of c‐FOS and is required for miR‐29b‐3p‐mediated neuronal differentiation inhibition. Our results suggest that atrophy‐associated circulating miR‐29b‐3p may mediate distal communication between muscle cells and neurons. Abstract : miR‐29b‐3p‐containing exosomes released from atrophied muscle can be transported via the circulation and transferred to neuronal cells. Increased miR‐29b‐3p levels in neuronal cells may lead to inhibition of neuronal differentiation.